2019
DOI: 10.1021/acsaem.9b01740
|View full text |Cite
|
Sign up to set email alerts
|

Band Structure Modification and Mass Fluctuation Effects of Isoelectronic Germanium-Doping on Thermoelectric Properties of ZrNiSn

Abstract: Less-expensive and abundantly available Hffree half-Heusler (HH) alloys are promising candidates for mid-temperature thermoelectric (TE). In the present work, we combine experimental outcomes with theoretical estimates to understand, design, and synthesize, Hf-free ZrNiSn 1−x Ge x based HH alloys with enhanced TE performance. A state-ofthe-art TE figure-of-merit (ZT) ∼ 0.92 at around 873 K was achieved for the optimal ZrNiSn 0.97 Ge 0.03 HH composition, wherein Ge atoms substitute Sn interstitial sites, as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 68 publications
6
38
1
Order By: Relevance
“…However, the band structure of pristine ZrNiSn is given in Figure S1, which shows semiconducting type behavior as suggested by earlier studies. ,, Therefore, the transition from semiconducting ZrNiSn to the semimetallic Zr 63 NbNi 64 Sn 64 is attributed to the electron doping via Nb (4d 4 5s 1 ) substitution at the Zr (4d 2 5s 2 ) site and is consistent with a previous report . The calculated total electron density of states (DOS) of Zr 63 NbNi 64 Sn 64 is compared with the calculated DOS of pristine ZrNiSn in Figure b. The contribution of the Nb atom in the total DOS of Zr 63 NbNi 64 Sn 64 is visible in the inset of Figure b.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…However, the band structure of pristine ZrNiSn is given in Figure S1, which shows semiconducting type behavior as suggested by earlier studies. ,, Therefore, the transition from semiconducting ZrNiSn to the semimetallic Zr 63 NbNi 64 Sn 64 is attributed to the electron doping via Nb (4d 4 5s 1 ) substitution at the Zr (4d 2 5s 2 ) site and is consistent with a previous report . The calculated total electron density of states (DOS) of Zr 63 NbNi 64 Sn 64 is compared with the calculated DOS of pristine ZrNiSn in Figure b. The contribution of the Nb atom in the total DOS of Zr 63 NbNi 64 Sn 64 is visible in the inset of Figure b.…”
Section: Resultssupporting
confidence: 86%
“…Muta et al found a similar kind of behavior for electrical conductivity in Nb-doped ZrNiSn Figure b displays the temperature-dependent Seebeck coefficient ( S ) of Zr 63 NbNi 64 Sn 64 at different carrier concentrations, which are compared with that of pristine ZrNiSn at a particular carrier concentration . It is clear from Figure b that | S | reduces with increasing carrier concentration and was found to be lower than that of pure ZrNiSn.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations